2020
DOI: 10.3390/cancers12010220
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Eicosapentaenoic Acid and Adipocyte Renin–Angiotensin System Inhibition on Breast Cancer Cell Inflammation and Migration

Abstract: Obesity is a major risk factor for breast cancer (BC). Obesity-related metabolic alterations such as inflammation and overactivation of the adipose renin–angiotensin system (RAS) may contribute to the progression of BC. Clinically used antihypertensive drugs such as angiotensin-converting enzyme inhibitors (ACE-I) and dietary bioactive components such as eicosapentaenoic acid (EPA) are known for their anti-inflammatory and adipose RAS blocking properties. However, whether EPA enhances the protective effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Paracrine interaction of adipokines with the cell-surface receptors on breast cancer cells, followed by the sustained activation of PI3K-Akt and Ras-ERK cell-signaling pathways, influence the metastatic behavior in breast cancer cells. To date, in vitro and in vivo studies have confirmed that obese or dysfunctional white adipocytes stimulate breast cancer progression by increasing the survival, growth, proliferation, migration, and invasion of breast cancer cells [ 69 , 83 , 106 , 107 , 108 , 109 ]. Other studies reported the direct influence of secreted factors on breast cancer progression.…”
Section: Obesity Inflammation and Breast Cancer—a Vicious Cyclementioning
confidence: 99%
“…Paracrine interaction of adipokines with the cell-surface receptors on breast cancer cells, followed by the sustained activation of PI3K-Akt and Ras-ERK cell-signaling pathways, influence the metastatic behavior in breast cancer cells. To date, in vitro and in vivo studies have confirmed that obese or dysfunctional white adipocytes stimulate breast cancer progression by increasing the survival, growth, proliferation, migration, and invasion of breast cancer cells [ 69 , 83 , 106 , 107 , 108 , 109 ]. Other studies reported the direct influence of secreted factors on breast cancer progression.…”
Section: Obesity Inflammation and Breast Cancer—a Vicious Cyclementioning
confidence: 99%
“…Wang et al (Wang et al, 2008) also found that angiotensin-converting enzyme inhibitors (ACEIs) and ARBs could inhibit the growth and angiogenesis of gastric cancer tumor models. Similarly, Nakamura et al (Nakamura et al, 2018), Regan et al (Regan et al, 2019), and Rasha et al (Rasha et al, 2020) found that the RAS system was involved in the regulation of certain cancer tumor microenvironments. For example, captopril reduces the expression of pro-inflammatory cytokines in breast cancer cell lines and ARB has a certain blocking effect on the immune suppression tumor microenvironment of colon cancer involved by RAS.…”
Section: Anti-hypertensive Drugs Affect Cancer Progression Through Mumentioning
confidence: 91%
“…The methanolic extract of Malva pseudolavatera leaves, which showed a promising selective anti-proliferative and pro-apoptotic effect on acute myeloid leukemia cell lines, determining PARP cleavage, cytochrome-c release, Bax/Bcl-2 ratio increase and ROS overproduction [19]; -Eicosapentaenoic acid, an ω-3 polyunsaturated fatty acid, which played a protective role, both alone and in combination with angiotensin-converting enzyme inhibitors, in attenuating adipocyte-induced proinflammatory cytokine expression and the migration of breast cancer cells in an in vitro model of obesity-induced breast cancer [20]; -Fucoidan, a sulphated polysaccharide derived from brown seaweed, whose combination with gemcitabine determined an enhanced pro-apoptotic and cell cycle-inhibitory activity on selected uterine carcinosarcoma and stromal sarcoma cell lines [21]; -Nicotin, whose mechanisms underlying the promotion of melanoma cell proliferation and migration mediated through α9-nAChR-initiated carcinogenic signaling and PD-L1 expression were reported by Nguyen et al [22]; -…”
mentioning
confidence: 99%
“…The other articles and reviews addressed further cancer-related issues relevant to types of compounds of a different nature, specifically: The methanolic extract of Malva pseudolavatera leaves, which showed a promising selective anti-proliferative and pro-apoptotic effect on acute myeloid leukemia cell lines, determining PARP cleavage, cytochrome-c release, Bax/Bcl-2 ratio increase and ROS overproduction [ 19 ]; Eicosapentaenoic acid, an ω-3 polyunsaturated fatty acid, which played a protective role, both alone and in combination with angiotensin-converting enzyme inhibitors, in attenuating adipocyte-induced proinflammatory cytokine expression and the migration of breast cancer cells in an in vitro model of obesity-induced breast cancer [ 20 ]; Fucoidan, a sulphated polysaccharide derived from brown seaweed, whose combination with gemcitabine determined an enhanced pro-apoptotic and cell cycle-inhibitory activity on selected uterine carcinosarcoma and stromal sarcoma cell lines [ 21 ]; Nicotin, whose mechanisms underlying the promotion of melanoma cell proliferation and migration mediated through α9-nAChR-initiated carcinogenic signaling and PD-L1 expression were reported by Nguyen et al [ 22 ]; The ethyl acetate fraction of the crude extract of Streptomyces sp. MUM256, isolated from mangrove soil in Malaysia, and the cyclic dipeptides contained whose ability to induce cell cycle arrest and apoptosis was demonstrated by Tan et al [ 23 ] in colon cancer cells; Manoalide, an antibiotic sesterterpenoid isolated from the marine sponge Luffariella variabilis , which preferentially inhibits the proliferation of oral cancer cells inducing apoptosis and DNA damages via oxidative stresses, such as intracellular ROS and MitoSOX/MitoMP [ 24 ]; λ-carrageenan, a family of linear sulfated polysaccharides, proven to enhance the effect of radiotherapy by suppressing the survival and invasiveness of different cancer cell lines in vitro and in vivo through the Rac GTPase-activating protein 1 pathway [ 25 ]; Ethanol, which was found to trigger a pro-survival autophagic response following the induction of oxidative and endoplasmic reticulum stress in colon cancer cells, and the activation of Nrf2 and HO-1 also leading to the acquisition of a more aggressive phenotype [ 26 ]; Colchicine, an alkaloid present in the medicinal plant Colchicum autumnale , whose enhanced anticancer effects and reduced cytotoxicity on colon cancer cells when delivered in the nanoformulated form was reported by AbouAitah et al [ 27 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation